2004
DOI: 10.1159/000076451
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Theory Is an Obstacle to the Progress of Clinical Research

Abstract: Psychometric theory is the basis for the development of assessment instruments in psychiatric research. However, the psychometric model appears to be largely inadequate in the clinical setting because of its lack of sensitivity to change and its quest for homogeneous components. Clinimetrics offers a viable alternative to psychometrics, both from a conceptual and a methodological viewpoint. Current diagnostic entities (DSM) are based on clinimetric principles, but their use is still influenced by psychometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 130 publications
(166 citation statements)
references
References 24 publications
7
158
0
1
Order By: Relevance
“…demoralisation, irritability, abnormal illness behaviour), identified in the course of extensive psychosomatic research, were found to be more frequent and also to have an independent connection with skin symptomatology when compared with DSM-IV diagnoses. Our findings lend support to the notion of endorsing sensitive assessment strategies encompassing sub-clinical symptomatology in performing clinical studies [45,46,47,48]. Our study suggests that psychosocial issues are an integral part of skin disease that deserves more attention in everyday practice.…”
Section: Discussionsupporting
confidence: 81%
“…demoralisation, irritability, abnormal illness behaviour), identified in the course of extensive psychosomatic research, were found to be more frequent and also to have an independent connection with skin symptomatology when compared with DSM-IV diagnoses. Our findings lend support to the notion of endorsing sensitive assessment strategies encompassing sub-clinical symptomatology in performing clinical studies [45,46,47,48]. Our study suggests that psychosocial issues are an integral part of skin disease that deserves more attention in everyday practice.…”
Section: Discussionsupporting
confidence: 81%
“…Despite the complex methodological problems involved in the assessment of anger and the recent criticism of the classical psychometric theory [44,45,46] also underlying some of the scales used here, this study demonstrates that symptoms related to lowered impulse control like anger attacks are more prevalent in male than in female depressed inpatients. Moreover, our results point out the need for the development of gender-specific diagnostic criteria in depression, which could be valuable for specific treatment approaches.…”
Section: Discussionmentioning
confidence: 63%
“…Our results suggest that manic/hypomanic symptoms and syndromes may be common in the community, do not necessarily entail clinical features and may lead to overdiagnosis of bipolar disorders in epidemiological studies [23, 24, 25, 26]. Subclinical manic/hypomanic symptoms may also be present in allegedly unipolar individuals and may have treatment implications.…”
Section: Discussionmentioning
confidence: 79%